2019
DOI: 10.5664/jcsm.7796
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Labelling Using Drug-Induced Sleep Endoscopy Improves Patient Selection for Mandibular Advancement Device Outcome: A Prospective Study

Abstract: Study Objectives: Mandibular advancement device (MAD) outcome varies between patients. We hypothesized that upper airway collapse sites, patterns, and degrees assessed during baseline drug-induced sleep endoscopy (DISE) affect MAD outcome. Methods: One hundred patients with obstructive sleep apnea (OSA) were included and underwent baseline type 1 polysomnography. MAD was fitted intraorally at fixed 75% maximal protrusion. A total of 72 patients completed 3-month follow-up polysomnography and baseline DISE. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 42 publications
8
72
0
1
Order By: Relevance
“…The results of the present prospective study, in a population of 14 patients who underwent MAD treatment followed by MMA surgery, show that a complete elimination of CCCp can be achieved by MMA surgery. This is of major importance, as CCCp is considered to be a negative predictive value for MAD treatment, UA surgery, and UA stimulation, and tends to be more difficult to alleviate compared to the other collapse patterns . In addition, when CCCp is present, higher CPAP pressure is needed to reopen the UA …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the present prospective study, in a population of 14 patients who underwent MAD treatment followed by MMA surgery, show that a complete elimination of CCCp can be achieved by MMA surgery. This is of major importance, as CCCp is considered to be a negative predictive value for MAD treatment, UA surgery, and UA stimulation, and tends to be more difficult to alleviate compared to the other collapse patterns . In addition, when CCCp is present, higher CPAP pressure is needed to reopen the UA …”
Section: Discussionmentioning
confidence: 99%
“…Previous research states that partial collapse is more favorable to be treated successfully than complete collapse, that anteroposterior collapse is more favorable than concentric collapse, and that unilevel collapse is more favorable than multilevel collapse . Severe laterolateral collapse has been linked to treatment failure in patients receiving MAD therapy or targeted interventions with multilevel surgery such as palatopharyngoplasty and tongue base surgery . A recent study observed 15 patients with CPAP failure and CCCp as a DISE baseline collapse pattern, and all patients underwent a uvulopalatopharyngoplasty with tonsillectomy (TE‐UPPP) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations